THE COURSE OF EPIDEMIC PAROTITIS DURING THE PERIOD OF RISING MORBIDITY, ACCORDING TO THE REPUBLICAN CENTER FOR INFECTIOUS DISEASES IN MAKHACHKALA - N. S. Karnaeva; L. U. Ulukhanova; A. M. Gusniev; A. G. Gadzhimirzaeva; S. G. Agayeva; R. M. Omarieva; S. K. Bilalova (LLC "Diagnostics and Vaccines", 2018)
The aim of the study was to study the course of epidemic parotitis in patients with a sharp increase in the incidence rate in Dagestan in 2017, and to analyze the coverage of vaccination against this infection.In the Republic of Dagestan, from January to December 2017, there was an increase in the incidence of mumps infection - 2,632 cases, in 2016 -148, in 2015 - 1 case. It turned out that 1492 (56.6%) of 2,632 patients with epidemic parotitis in 2017 were not vaccinated.Clinical and laboratory monitoring of 449 patients with epidemic parotitis hospitalized in the Republican Center for Infectious Diseases was carried out. The greatest number of cases was between the ages of 12 and 35 years. The clinical picture of parotitis infection in adults did not differ from that of children. First parotid glands are affected, then the lesions of other glandular organs are joined - pancreatitis (51.2%), orchitis (32%) and CNS - meningitis (16%). Outcomes of the disease were favorable.